Full-degradable multi-layer composite structure skull repair net and preparation method thereof

Through a fully degraded multi-layer composite structure skull repair net, combined with dense collagen cast membrane, zinc alloy mesh structure and porous electrospun collagen membrane, the problems of non-degradable and insufficient mechanical support of existing skull repair materials are solved, and the dual improvement of biological activity and mechanical properties of skull repair is achieved.

CN119896558APending Publication Date: 2025-04-29UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411841901.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing skull repair materials have problems such as non-degradable, insufficient mechanical support, poor biological activity and easy infection, which are difficult to meet the needs of patients with skull defects.

Method used

The fully degraded multi-layer composite structure skull repair net is adopted, including the outer dense collagen cast film, the intermediate zinc alloy mesh structure and the inner porous electrospun collagen membrane. It is prepared through cross-linking and bonding technology to ensure that the material slowly degrades during the skull repair process and promotes skull growth.

Benefits of technology

This material has excellent biological activity and good mechanical support properties, which can effectively promote skull repair and regeneration, reduce the risk of infection, and adapt to the customized needs of skull defect parts in different patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896558A_ABST
    Figure CN119896558A_ABST
Patent Text Reader

Abstract

The invention relates to the field of skull repair, and provides a fully-degradable multi-layer composite structure skull repair net and a preparation method thereof.According to the skull repair net, a compact collagen film layer is prepared on the outer surface through solvent volatilization of a solution, and a porous electrostatic spinning collagen film layer is prepared on the inner surface through an electrostatic spinning technology; the middle layer is prepared into a degradable alloy net structure through a laser cutting technology, and the middle layer is bonded through a 1% (w / v) collagen aqueous solution to form the skull repair net with the multi-layer composite structure. One side of the compact layer is used for shielding fibroblast migration, and one side of the porous microfiber is used for promoting cell adhesion proliferation and osteogenesis and blood vessel formation. The middle alloy net-shaped structure provides mechanical support, slowly degrades and releases Zn < 2 + > and promotes bone repair, in addition, the hollow parallel arc design can simultaneously realize out-of-plane deformation in the direction perpendicular to the net-shaped structure and stretching or compression deformation under the action of in-plane stress, large-area falling in the degradation process is avoided, and the secondary operation risk is avoided. Good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of skull repair, and in particular to a fully degradable multi-layer composite skull repair net and a preparation method thereof. Background Art

[0002] The skull is a key structure that protects important organs such as the brain, but it is easy to cause skull damage due to accidents, diseases and other reasons. Skull defects are common sequelae of craniocerebral trauma in clinical practice. They not only cause skull deformities in patients, affect patients' psychology, but also may cause nervous system damage in severe cases. However, the application of appropriate skull repair materials has positive significance for the recovery of skull morphology and brain function in patients. Skull repair materials have gone through stages such as autologous bone, plexiglass, silicone rubber, bone cement, titanium alloy, and polyetheretherketone, but these materials all have certain defects and cannot fully meet the needs of patients with skull defects. For example, although autologous bone rarely has rejection reactions after surgery and has a low risk of infection, autologous bone materials are limited, tissue preservation and processing processes are cumbersome, and application conditions are restricted in various aspects. It is only suitable for the repair of small skull defects. Titanium mesh has the advantages of light weight, good stability, and good biocompatibility, but titanium mesh has poor plasticity during surgery, is not easy to adjust, and is prone to artifacts that affect image effects, and it is difficult to judge the presence of hematomas or tumors near the implant. Polyetheretherketone (PEEK) material has good imaging compatibility, no artifacts, and its elasticity and energy absorption properties are closer to bones than titanium. However, it has poor integration with surrounding tissues, is prone to infection and formation of subcutaneous effusion, and has a high postoperative infection rate.

[0003] In addition, the skull repair scaffolds currently used clinically all have the problem of being non-degradable. If they are present in the skull defect area for a long time, they are prone to infection and are not conducive to skull regeneration. In order to promote skull repair and regeneration, some research teams have developed commercial collagen membranes, but this commercial collagen membrane lacks layered structural design and effective mechanical support, and it degrades quickly, so its effect on skull regeneration is limited. Degradable metal scaffolds not only have good mechanical support, but also the degraded ions have osteogenic or antibacterial properties. However, since metal scaffolds usually undergo a certain amount of plastic deformation in clinical applications, it may cause excessive local stress in the scaffold, and the concentration of ion release during the degradation process is uncontrollable, causing cytotoxicity. Therefore, it is of great clinical significance to develop a bone substitute material with both excellent biological and mechanical properties for repairing skull defects.

[0004] Aiming at the special environment of skull defect and the characteristics of bioactive materials and degradable metal stents, the present invention proposes a fully degradable multi-layer composite skull repair mesh and a preparation process. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a fully degradable multi-layer composite structure skull repair mesh and preparation method. Different from the non-degradable scaffolds and commercially available bone repair collagen membranes used in clinical practice, the composite structure not only has a suitable degradation rate, but also has sufficient mechanical support and good biological activity, ensuring that it slowly degrades during skull repair while promoting skull growth. In addition, this implant can be customized according to the shape of the patient's skull defect and better fit the patient's skull injury site.

[0006] The present invention adopts the following technical solution:

[0007] In one aspect, the present invention provides a method for preparing a fully degradable multi-layer composite structure skull repair mesh, comprising:

[0008] S1. preparing dense collagen casting membrane;

[0009] S2, preparing an alloy network structure;

[0010] S3, preparing porous electrospun collagen membrane;

[0011] S4, laying the alloy mesh structure obtained in step S2 on the surface of the dense collagen cast film obtained in step S1, dripping adhesive, and then laminating the porous electrospun collagen membrane obtained in step S3 on the surface of the alloy mesh structure, pressing, and putting the three-layer structure into a constant temperature incubator for drying, so as to obtain the fully degradable multi-layer composite structure skull repair mesh;

[0012] There is no order of precedence for steps S1, S2 and S3.

[0013] Any possible implementation as described above further provides an implementation, in step S1, the method for preparing a dense collagen casting film comprises:

[0014] S11, dissolving collagen in hexafluoroisopropanol solution, stirring to ensure complete dissolution to form a collagen solution;

[0015] S12, placing the prepared collagen solution into a vacuum pump, extracting gas, and removing bubbles in the collagen solution;

[0016] S13, spreading a layer of aluminum foil on the culture dish, pouring the collagen solution on the surface of the aluminum foil, and obtaining a dense collagen film after the solvent evaporates;

[0017] S14, immersing the collagen cast obtained in step S13 in an EDC and NHS anhydrous ethanol solution for cross-linking.

[0018] Any possible implementation described above further provides an implementation:

[0019] In S11, 1.6 g of collagen is dissolved in 20 ml of hexafluoroisopropanol solution according to the proportion, and stirred for more than 12 hours to completely dissolve and form a collagen solution with a concentration of 8% (w / v);

[0020] In S12, the collagen solution is placed in a vacuum pump to extract gas for 30 minutes;

[0021] In S14, the concentrations of EDC and NHS were 20 mM and 10 mM, respectively.

[0022] Any possible implementation as described above further provides an implementation, in step S3, the method for preparing a porous electrospun collagen membrane comprises:

[0023] S31, dissolving type I collagen in a hexafluoroisopropanol solution to form a collagen solution;

[0024] S32, after the collagen solution obtained in step S31 is magnetically stirred for a set time, the collagen solution is extracted with a syringe and fixed on a constant current pump, the positive electrode of the high-voltage electrostatic generator is connected to the needle, the negative electrode is connected to the receiving plate, and a layer of foil is rolled on the receiving roller to receive the electrospun fibers;

[0025] S33, setting the injection flow rate, receiving rotation speed, receiving distance and voltage, starting spinning, removing the box paper after spinning is completed, and obtaining an electrospun collagen membrane;

[0026] S34, immersing the electrospun collagen membrane prepared in step S33 in an EDC and NHS anhydrous ethanol solution for cross-linking.

[0027] Any possible implementation described above further provides an implementation:

[0028] In S31, the concentration of collagen formed was 8% (w / v);

[0029] In S32, the collagen solution obtained in step S31 is magnetically stirred for more than 24 hours, and the foil is aluminum foil;

[0030] In S33, the injection flow rate is set to 0.05 mL / min, the receiving speed is set to 200 r / min, the receiving distance is set to 15 cm, and the voltage is set to ﹢19 V / ﹣2 V;

[0031] In S34, the concentrations of EDC and NHS were 20 mM and 10 mM, respectively.

[0032] According to any possible implementation described above, a further implementation is provided, in step S2, the method for preparing the alloy network structure is:

[0033] S21, heat treating the alloy ingot to obtain a homogenized structure;

[0034] S22, machining the ingot to obtain a template with a first set thickness;

[0035] S23, rolling the template into a thin plate of a second set thickness by combining hot rolling and cold rolling;

[0036] S24. Cut the rolled 0.1 mm thick alloy sheet into a set mesh structure using laser cutting technology, and clean and remove the surface oxide layer.

[0037] Any possible implementation described above further provides an implementation:

[0038] In S21, the heat treatment is: keeping the temperature at 350°C for 2 hours and then cooling with the furnace;

[0039] In S22, the first set thickness is 1 cm;

[0040] In S23, the second set thickness is 0.1 mm;

[0041] In S24, washing is performed using 0.3 M acetic acid.

[0042] Any possible implementation described above further provides an implementation, in which the specific method of step S4 includes:

[0043] S41, after the dense collagen cast membrane is cross-linked in the EDC-NHS solution for more than 6 hours, it is taken out, rinsed with deionized water for 5 minutes, and then spread flat in a plastic culture dish, placed in a constant temperature incubator for a certain period of time, and taken out;

[0044] S42, placing the alloy network structure on the surface of the dense collagen casting film treated in step S41, and dripping a 1% (w / v) collagen aqueous solution for bonding;

[0045] S43, attaching the electrospun collagen membrane that has been cross-linked in the EDC-NHS solution for more than 24 hours and dried to the upper surface of the alloy network structure treated in step S42, and pressing to squeeze out excess collagen aqueous solution;

[0046] S44. After the three-layer structure is completely bonded, place it in a constant temperature incubator to dry.

[0047] On the other hand, the present invention also provides a fully degradable multi-layer composite skull repair mesh, including an outer layer of dense collagen mold, a middle layer of alloy mesh structure and an inner layer of porous electrospun collagen membrane.

[0048] As for any possible implementation described above, there is further provided an implementation, wherein the skull repair mesh is prepared by the above method.

[0049] As any possible implementation described above, there is further provided an implementation, wherein the alloy mesh structure is made of zinc alloy.

[0050] Any possible implementation as described above, further provides an implementation, in which the mesh structure adopts an internal hollow parallel arc design, which can simultaneously realize out-of-plane deformation perpendicular to the direction of the mesh structure and tensile or compressive deformation under the action of in-plane stress, and ensure that the parallel arc design will not cause large-scale detachment of the mesh structure during the degradation process.

[0051] The beneficial effects of the present invention are:

[0052] The multi-layer composite structure skull repair mesh provided by the present invention has excellent biological activity and good mechanical support performance. Its surface dense layer has better fibroblast barrier ability than the single fiber structure, and the collagen matrix protects the middle layer from severe corrosion caused by stress concentration due to pre-deformation. Its porous microfiber side is through the bionic extracellular matrix and sustainable Zn 2+ Release is beneficial to promote cell adhesion, proliferation and differentiation, and enhance osteogenesis and angiogenesis. The middle layer of zinc alloy mesh structure not only plays a certain mechanical support role, but also the parallel arc design during the degradation process prevents it from falling off in a large area, and always maintains a uniform structure. In addition, the skull repair mesh can be customized according to the patient's skull defect site, make appropriate pre-deformation, fit the patient's skull shape well, and avoid psychological problems caused by head deformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 Shown is an image of a dense collagen cast in an example.

[0054] Figure 2 Shown is the SEM image of the electrospun collagen membrane after cross-linking in the example.

[0055] Figure 3 Shown is an image of a skull repair mesh composed of three layers of structure in the embodiment. DETAILED DESCRIPTION

[0056] The specific embodiments of the present invention will be described in detail below in conjunction with specific drawings. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.

[0057] The inventive ideas of the present invention are as follows:

[0058] 1. In the design of the composite scaffold, the bone growth problem in the skull defect area is first considered. In order to promote the proliferation of bone cells and prevent the growth of unnecessary connective tissue cells in the bone defect area, a dense collagen film is formed on the outside of the surface layer by evaporating the collagen solution solvent. On the one hand, the biological activity of collagen is used to promote the proliferation and differentiation of osteoblasts, and on the other hand, the dense collagen film prevents the migration of fibroblasts. At the same time, in order to further promote the rapid growth of bone in the defect area, a porous electrospinning collagen membrane is prepared by electrospinning technology. As the inner side of the surface layer, the porous microfiber channel realizes the biomimetic extracellular matrix and sustainable Zn 2+ Released, promoting osteoblast adhesion, enhancing osteogenesis and angiogenesis.

[0059] 2. Taking into full account the poor mechanical properties of the collagen membrane, in order to maintain the bone formation space in the defect area, and considering the good mechanical properties and moderate degradation rate of zinc alloy, a zinc alloy mesh structure is introduced into the middle layer to provide stable mechanical support, while ensuring slow degradation within a certain period of time to promote skull repair and regeneration. The specific implementation method is the design of a zinc alloy mesh structure, in which the connecting area between the circular holes adopts a parallel circular arc line structure design, so that the original load-bearing structure can not only achieve out-of-plane deformation perpendicular to the direction of the mesh structure, but also withstand tensile or compressive deformation under the action of in-plane stress, and has good mechanical support. At the same time, the parallel arc line structure design can effectively avoid the collapse of the mesh structure caused by stress concentration in some regional structures due to deformation, resulting in accelerated degradation, and play a role in stabilizing the mesh support structure.

[0060] 3. In the preparation process of the multi-layer composite structure, due to the lack of stable bonding between collagen and zinc alloy, in order to ensure their firm bonding, it is proposed to use collagen aqueous solution as an adhesive, and bond the inner and outer sides of the surface layer through a mesh structure to finally obtain a multi-layer composite structure skull repair mesh with a stable morphology.

[0061] The present invention provides a method for preparing a fully degradable multi-layer composite structure skull repair mesh, comprising:

[0062] S1. preparing dense collagen casting membrane;

[0063] S2, preparing an alloy network structure;

[0064] S3, preparing porous electrospun collagen membrane;

[0065] S4, laying the alloy mesh structure obtained in step S2 on the surface of the dense collagen cast film obtained in step S1, dripping adhesive, and then laminating the porous electrospun collagen membrane obtained in step S3 on the surface of the alloy mesh structure, pressing, and putting the three-layer structure into a constant temperature incubator for drying, so as to obtain the fully degradable multi-layer composite structure skull repair mesh;

[0066] There is no order of precedence for steps S1, S2 and S3.

[0067] In a specific embodiment, in step S1, the method for preparing a dense collagen film comprises:

[0068] S11, dissolving collagen in hexafluoroisopropanol solution, stirring to ensure complete dissolution to form a collagen solution;

[0069] S12, placing the prepared collagen solution into a vacuum pump, extracting gas, and removing bubbles in the collagen solution;

[0070] S13, spreading a layer of aluminum foil on the culture dish, pouring the collagen solution on the surface of the aluminum foil, and obtaining a dense collagen film after the solvent evaporates;

[0071] S14, immersing the collagen cast obtained in step S13 in an EDC and NHS anhydrous ethanol solution for cross-linking.

[0072] In a specific embodiment,

[0073] In S11, 1.6 g of collagen is dissolved in 20 ml of hexafluoroisopropanol solution according to the proportion, and stirred for more than 12 hours to completely dissolve and form a collagen solution with a concentration of 8% (w / v);

[0074] In S12, the collagen solution is placed in a vacuum pump to extract gas for 30 minutes;

[0075] In S14, the concentrations of EDC and NHS were 20 mM and 10 mM, respectively.

[0076] In a specific embodiment, in step S3, the method for preparing a porous electrospun collagen membrane comprises:

[0077] S31, dissolving type I collagen in a hexafluoroisopropanol solution to form a collagen solution;

[0078] S32, after the collagen solution obtained in step S31 is magnetically stirred for a set time, the collagen solution is extracted with a syringe and fixed on a constant current pump, the positive electrode of the high-voltage electrostatic generator is connected to the needle, the negative electrode is connected to the receiving plate, and a layer of foil is rolled on the receiving roller to receive the electrospun fibers;

[0079] S33, setting the injection flow rate, receiving rotation speed, receiving distance and voltage, starting spinning, removing the box paper after spinning is completed, and obtaining an electrospun collagen membrane;

[0080] S34, immersing the electrospun collagen membrane prepared in step S33 in an EDC and NHS anhydrous ethanol solution for cross-linking.

[0081] In a specific embodiment,

[0082] In S31, the concentration of collagen formed was 8% (w / v);

[0083] In S32, the collagen solution obtained in step S31 is magnetically stirred for more than 24 hours, and the foil is aluminum foil;

[0084] In S33, the injection flow rate is set to 0.05 mL / min, the receiving speed is set to 200 r / min, the receiving distance is set to 15 cm, and the voltage is set to ﹢19 V / ﹣2 V;

[0085] In S34, the concentrations of EDC and NHS were 20 mM and 10 mM, respectively.

[0086] In a specific embodiment, in step S2, the method for preparing the alloy network structure is:

[0087] S21, heat treating the alloy ingot to obtain a homogenized structure;

[0088] S22, machining the ingot to obtain a template with a first set thickness;

[0089] S23, rolling the template into a thin plate of a second set thickness by combining hot rolling and cold rolling;

[0090] S24. Cut the rolled 0.1 mm thick alloy sheet into a set mesh structure using laser cutting technology, and clean and remove the surface oxide layer.

[0091] In a specific embodiment,

[0092] In S21, the heat treatment is: keeping the temperature at 350°C for 2 hours and then cooling with the furnace;

[0093] In S22, the first set thickness is 1 cm;

[0094] In S23, the second set thickness is 0.1 mm;

[0095] In S24, washing is performed using 0.3 M acetic acid.

[0096] In a specific embodiment, the specific method of step S4 includes:

[0097] S41, after the dense collagen cast membrane is cross-linked in the EDC-NHS solution for more than 6 hours, it is taken out, rinsed with deionized water for 5 minutes, and then spread flat in a plastic culture dish, placed in a constant temperature incubator for a certain period of time, and taken out;

[0098] S42, placing the alloy network structure on the surface of the dense collagen casting film treated in step S41, and dripping a 1% (w / v) collagen aqueous solution for bonding;

[0099] S43, attaching the electrospun collagen membrane that has been cross-linked in the EDC-NHS solution for more than 24 hours and dried to the upper surface of the alloy network structure treated in step S42, and pressing to squeeze out excess collagen aqueous solution;

[0100] S44. After the three-layer structure is completely bonded, place it in a constant temperature incubator to dry.

[0101] The embodiment of the present invention provides a fully degradable multi-layer composite skull repair mesh, which includes an outer layer of dense collagen casting mold, a middle layer of alloy mesh structure and an inner layer of porous electrospun collagen membrane.

[0102] In a specific embodiment, the skull repair mesh is prepared by the above method.

[0103] Example

[0104] A method for preparing a fully degradable multi-layer composite structure skull repair mesh, comprising:

[0105] 1. Prepare a dense collagen film on the outside of the surface layer. First, dissolve 1.6g of collagen in 20ml of hexafluoroisopropanol solution and stir for more than 12 hours to ensure complete dissolution to form a collagen solution with a concentration of 8% (w / v). Secondly, put the prepared collagen solution into a vacuum pump and extract the gas for 30 minutes to remove the bubbles in the collagen solution. Then, spread a layer of aluminum foil on the culture dish, pour the collagen solution on the surface of the aluminum foil, and after the solvent evaporates, a dense collagen film can be obtained. Figure 1 To prevent the collagen membrane from excessively swelling when placed in an aqueous solution, the collagen membrane was immersed in a 20 mM EDC and 10 mM NHS anhydrous ethanol solution for 6 hours for cross-linking, in preparation for the subsequent preparation of a multi-layer composite structure skull repair mesh.

[0106] 2. Prepare a zinc-lithium alloy network structure in the middle layer. First, heat treat the zinc-lithium alloy ingot, keep it at 350℃ for two hours, and then cool it in the furnace to obtain a homogenized structure. Secondly, machine the ingot to obtain a template with a thickness of 1cm, and then use a combination of hot rolling and cold rolling to roll the plate to 0.1mm to obtain a thin plate with good mechanical properties. Finally, use laser cutting technology to cut the rolled 0.1mm thick zinc alloy sheet into a network structure with good ductility, and remove the surface oxide layer by cleaning with 0.3M acetic acid.

[0107] 3. Prepare a porous electrospun collagen membrane on the inner side of the surface layer. First, dissolve type I collagen in a hexafluoroisopropanol solution to form a collagen solution with a collagen concentration of 8% (w / v). After magnetic stirring for 24 hours, use a syringe to extract 10 ml of collagen spinning solution and fix it on a constant current pump. Connect the positive electrode of the high-voltage electrostatic generator to the needle, and the negative electrode to the receiving plate. A layer of aluminum foil is rolled up on the receiving roller to receive the electrospun fibers. Set the push flow rate to 0.05 mL / min, the receiving speed to 200 r / min, the receiving distance to 15 cm, the high voltage to ﹢19 V / ﹣2 V, and after spinning is completed, remove the aluminum foil to obtain an electrospun collagen membrane. The electrospun collagen membrane was then immersed in a 20 mM EDC and 10 mM NHS anhydrous ethanol solution for 24 hours for further cross-linking treatment. The SEM image of the cross-linked electrospun collagen membrane is shown in the figure. Figure 2 As shown, preparation is made for the subsequent multi-layer composite structure skull mesh preparation.

[0108] 4. Preparation of multi-layer composite skull repair mesh. First, the electrospun collagen membrane was taken out from the EDC-NHS solution 24 hours after cross-linking, and then placed in 20%, 50%, and 80% (v / v) PBS / anhydrous ethanol mixed solutions for gradient washing, soaking in the mixed solution for 5 minutes each time, and then soaked in 0.01M PBS solution for 5 minutes before taking it out, placing it in a plastic culture dish to dry naturally and wait for further processing. At the same time, prepare a collagen aqueous solution with a collagen concentration of 1% (w / v) as an adhesive. Secondly, the collagen cast membrane was taken out after cross-linking in the EDC-NHS solution for 6 hours, rinsed with deionized water for 5 minutes, and then spread on a plastic culture dish, placed in a 37°C constant temperature incubator for 10 minutes, and then taken out immediately. Then, a zinc alloy mesh structure is placed on the surface of the collagen cast film, and a drop of 1% (w / v) collagen aqueous solution is added with a rubber-tipped dropper for bonding. Subsequently, the electrospun collagen membrane is attached to the surface of the zinc alloy mesh structure, and tweezers are used to gently press and discharge the excess collagen aqueous solution. After the three-layer structure is completely attached, it is placed in a 37°C constant temperature incubator to dry to obtain a multi-layer composite skull repair mesh. Figure 3 shown.

[0109] The skull repair net of the present invention has a dense collagen membrane on the outer surface, and its dense side not only has good fibroblast barrier ability, but also can protect the zinc alloy mesh structure from serious corrosion due to pre-deformation; the porous collagen fiber spinning membrane on the inner surface, its porous microfiber side can promote osteoblast adhesion, proliferation and differentiation through bionic extracellular matrix, collagen degradation and zinc ion release, and has good osteogenesis and angiogenesis ability; the zinc alloy mesh structure in the middle layer can not only play a certain mechanical support role, but also slowly release Zn 2+, promoting osteogenesis and angiogenesis; the connecting lines between units are arc-bent structures, which can achieve tensile or compressive deformation under stress, and add parallel arc lines to ensure that there will be no large-scale shedding during the degradation process, causing the risk of secondary surgery; the inner and outer surfaces are cross-linked with EDC-NHS cross-linking agent, which will not degrade quickly and prevent Zn 2+ Burst release causes cytotoxicity.

[0110] The skull repair bracket of the present invention can be customized according to the defective part of the skull of the patient, so that it is easier to adhere to the skull shape and can be more firmly in contact with and fixed to the human skull. This multi-layer composite structure zinc alloy skull repair mesh developed by combining the technology of forming a dense cast film by solvent evaporation and an electrostatically spun porous collagen film not only has a stable mechanical support function, but also has good biological activity, which greatly meets the clinical needs of patients and has good application prospects.

[0111] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.

Claims

1. A method for preparing a fully degradable multi-layer composite structure skull repair mesh, characterized in that: The method comprises: S1. preparing dense collagen membrane; S2, preparing an alloy network structure; S3, preparing porous electrospun collagen membrane; S4, laying the alloy mesh structure obtained in step S2 on the surface of the dense collagen cast film obtained in step S1, dripping adhesive, and then laminating the porous electrospun collagen membrane obtained in step S3 on the surface of the alloy mesh structure, pressing, and waiting for the three-layer structure to be completely laminating and drying, thereby obtaining the fully degradable multi-layer composite structure skull repair mesh; There is no order of precedence for steps S1, S2 and S3.

2. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 1, characterized in that: In step S1, the method for preparing a dense collagen cast film comprises: S11, dissolving collagen in a hexafluoroisopropanol solution, stirring, and completely dissolving to form a collagen solution; S12, placing the prepared collagen solution into a vacuum pump to remove bubbles in the collagen solution; S13, laying a layer of foil on the culture dish, pouring the collagen solution on the surface of the foil, and obtaining a dense collagen film after the solvent evaporates; S14, immersing the collagen cast obtained in step S13 in an anhydrous ethanol solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide EDC and N-hydroxysuccinimide NHS for cross-linking.

3. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 2, characterized in that: In S11, collagen is dissolved in a hexafluoroisopropanol solution according to a certain proportion, and stirred for more than 12 hours to completely dissolve and form a collagen solution with a concentration of 8% (w / v); In S12, the collagen solution is placed in a vacuum pump to extract gas for 30 minutes; In S14, the concentrations of EDC and NHS were 20 mM and 10 mM, respectively.

4. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 1, characterized in that: In step S3, the method for preparing a porous electrospun collagen membrane comprises: S31, dissolving type I collagen in a hexafluoroisopropanol solution to form a collagen solution; S32, after the collagen solution obtained in step S31 is magnetically stirred for a set time, the collagen solution is extracted with a syringe and fixed on a constant current pump, the positive electrode of the high-voltage electrostatic generator is connected to the needle, the negative electrode is connected to the receiving plate, and a layer of foil is rolled on the receiving roller to receive the electrospun fibers; S33, setting the injection flow rate, receiving speed, receiving distance and voltage, starting spinning, and removing the foil after spinning is completed to obtain an electrospun collagen membrane; S34, immersing the electrospun collagen membrane prepared in step S33 in an EDC and NHS anhydrous ethanol solution for cross-linking.

5. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 4, characterized in that: In S31, the concentration of collagen formed was 8% (w / v); In S32, the collagen solution obtained in step S31 is magnetically stirred for more than 24 hours, and the foil is aluminum foil; In S33, the set injection flow rate is 0.05 mL / min, the receiving speed is 200 r / min, the receiving distance is 15 cm, and the voltage is ﹢19 V / ﹣2 V; In S34, the concentrations of EDC and NHS were 20 mM and 10 mM, respectively.

6. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 1, characterized in that: In step S2, the method for preparing the alloy network structure is: S21, heat treating the alloy ingot to obtain a homogenized structure; S22, machining the alloy ingot to obtain a template with a first set thickness; S23, rolling the template into a thin plate of a second set thickness by combining hot rolling and cold rolling; S24, cutting the rolled thin plate into a set mesh structure by using laser cutting technology, and cleaning and removing the surface oxide layer.

7. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 6, characterized in that: In S21, the heat treatment is: keeping the temperature at 350° C. for 2 hours and then cooling with the furnace; In S22, the first set thickness is 1 cm; In S23, the second set thickness is 0.05-0.5 mm; In S24, washing is performed using 0.3 M acetic acid.

8. The method for preparing the fully degradable multi-layer composite structure skull repair mesh according to claim 1, characterized in that: The specific method of step S4 includes: S41, after the dense collagen cast membrane is cross-linked in the EDC-NHS solution for more than 6 hours, it is taken out, rinsed with deionized water, and then spread flat in a plastic culture dish, placed in a constant temperature incubator for a certain period of time, and taken out; S42, placing the alloy network structure on the surface of the dense collagen casting film treated in step S41, and dripping a 1% (w / v) collagen aqueous solution for bonding; S43, attaching the electrospun collagen membrane that has been cross-linked in the EDC-NHS solution for more than 24 hours and dried to the upper surface of the alloy network structure treated in step S42, and pressing to squeeze out excess collagen aqueous solution; S44. After the three-layer structure is completely bonded, place it in a constant temperature incubator to dry.

9. A fully degradable multi-layer composite structure skull repair mesh, characterized in that: The skull repair mesh comprises a dense collagen mold of an outer layer, an alloy mesh structure of a middle layer, and a porous electrospun collagen membrane of an inner layer; the skull repair mesh is prepared by the method according to any one of claims 1 to 8.

10. The fully degradable multi-layer composite skull repair mesh according to claim 9, characterized in that: The alloy mesh structure is made of zinc alloy; the mesh structure adopts a parallel arc design with internal hollowing, and simultaneously realizes out-of-plane deformation perpendicular to the mesh structure direction and tensile or compressive deformation under the action of in-plane stress.